ANALISIS KESALAHAN PESERTA DIDIK PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN NILAI MUTLAK LINEAR SATU VARIABEL DI KELAS X SMA NEGERI 1 BANGKINANG KOTA (Universitas PGRI Sumatera Barat, 2017)
This study aimed to describe aspects of the mistakes made by the students of class X SMA Negeri 1 Bangkinang City in solving problems related to materials Equations and Inequalities Value Absolute Linear Single Variable, describing the most common mistake made students of class X SMA Negeri 1 Bangkinang City in solving problems related material Absolute Value Equations and Inequalities Linear Single variable, and to know how big the error percentage of students in each aspect of error. Method in this research is descriptive qualitative and quantitative desriptif. Qualitative description that describes the mistakes made kesalaha-learners by using words. While quantitative descriptive is describing big mistakes do learners using numbers. Suharsimi Arikunto (2006: 12) argues that research is a quantitative research approaches are required to use a lot of numbers, ranging from data collection, interpretation of these data, and displays the results. According Sumanto (1995: 77) descriptive study tried to describe and interpret what is there (could about the condition or relationship, a growing opinion, the ongoing process, due to actual or emerging inclinations). Based on the results of diagnostic tests on the material equations and linear inequalities absolute value of the variable obtained that there are students who make mistakes in solving problems related to the material. Mistakes made by learners consists of 71% false beliefs and misconceptions 69%